2022
DOI: 10.1155/2022/4446805
|View full text |Cite
|
Sign up to set email alerts
|

ZNF165 Is Involved in the Regulation of Immune Microenvironment and Promoting the Proliferation and Migration of Hepatocellular Carcinoma by AhR/CYP1A1

Abstract: The strong tumorigenic capacity and treatment resistance made hepatocellular carcinoma (HCC) a huge threat to public health. ZNF165, the kruppel family of zinc-finger-containing transcription factors, is expressed in HCC; however, its specific role in HCC and the molecular mechanism are yet to be elucidated. In this study, we observed that ZNF165 was overexpressed in liver cancer tissues and the immune microenvironment; higher ZNF165 expression was correlated with lower overall survival in liver cancer patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…constructed a risk model based on CHMP4C to predict the tumor immune microenvironment (TIME) and guide the chemotherapy and immunotherapy of BLCA ( 42 ). ZNF165 is a functionally enigmatic cancer/testis (CT) antigen whose expression is usually restricted to germ cells but is aberrantly activated in tumors and is associated with the prognosis of a variety of tumors, mediated mainly by participating in the regulation of the TIME ( 43 , 44 ). STAP2 promotes the generation of long-term functional memory CD8+ T cells by preventing terminal effector differentiation ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…constructed a risk model based on CHMP4C to predict the tumor immune microenvironment (TIME) and guide the chemotherapy and immunotherapy of BLCA ( 42 ). ZNF165 is a functionally enigmatic cancer/testis (CT) antigen whose expression is usually restricted to germ cells but is aberrantly activated in tumors and is associated with the prognosis of a variety of tumors, mediated mainly by participating in the regulation of the TIME ( 43 , 44 ). STAP2 promotes the generation of long-term functional memory CD8+ T cells by preventing terminal effector differentiation ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…We then assessed the transcriptional activity of the CYP1A1 promoter using a dual luciferase reporter assay and found enhanced transcriptional activity of CYP1A1 in the PM2.5 exposed cells compared with the control cells ( Figure 9B ). Previous studies have shown that the expression of some cytochrome P450 family genes are regulated by transcription factors (TFs) ( Degrelle et al, 2022 ; Liu et al, 2022 ; Rannug, 2022 ; Shivaram et al, 2023 ). Thus, whether PM2.5 modified CYP1A1 expression via TFs in trophoblast cells was assessed.…”
Section: Resultsmentioning
confidence: 99%
“…The characterization of tryptophan metabolism and its dysregulation in fibroids revealed an increased expression of CYP1B1 mRNA, a marker of AhR activation [ 88 , 94 ]. ZNF165 (a member of the Kruppel family of zinc-finger-containing transcription factors), which is overexpressed in liver cancer tissues and the immune microenvironment, promotes the proliferation and migration of hepatocellular carcinoma by activating the tryptophan/kynurenine/AhR/CYP1A1 axis and by boosting the expression of CYP1A1 [ 95 ].…”
Section: Gut Microbiota Indole Products and Their Interaction With Cy...mentioning
confidence: 99%